2018
DOI: 10.1016/j.bjm.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Shigatoxigenic and atypical enteropathogenic Escherichia coli in fish for human consumption

Abstract: Shigatoxigenic and enteropathogenic Escherichia coli with virulence and multidrug resistance profile were isolated from Nile tilapia. This study finding is of great importance to public health because they help understand this pathogen epidemiology in fish and demonstrate how these animals can transmit E. coli related diseases to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
(40 reference statements)
1
19
0
2
Order By: Relevance
“…STEC genes were also reported in E. coli from fish of pay‐to‐fish ponds in SP (Ribeiro et al ; Cardozo et al ) and from stable flies ( Stomoxys calcitrans ) (Castro et al ).…”
Section: Occurrence Of Stec In Animalsmentioning
confidence: 83%
See 4 more Smart Citations
“…STEC genes were also reported in E. coli from fish of pay‐to‐fish ponds in SP (Ribeiro et al ; Cardozo et al ) and from stable flies ( Stomoxys calcitrans ) (Castro et al ).…”
Section: Occurrence Of Stec In Animalsmentioning
confidence: 83%
“…Additionally, Gioia‐Di Chiacchi et al (, ) reported the detection of tEPEC/STEC hybrid strains isolated from small‐size psittacine birds raised as pets, carrying the stx2f subtype and belonging to the serotype O137:H6, previously associated with HUS. STEC strains isolated from fish farm and free fish by Cardozo et al () had the stx2a , stx2c and stx2d subtypes.…”
Section: Virulence Of Stec Isolated From Animalmentioning
confidence: 99%
See 3 more Smart Citations